Data-knowledge-driven diagnosis method for sludge bulking of wastewater treatment process. (February 2021) - Han, Hong-Gui; Dong, Li-Xin; Qiao, Jun-Fei
Abstract: Sludge bulking is very common in wastewater treatment process (WWTP), which will degrade the operation performance or even destroy the process. In order to diagnose sludge bulking accurately, a data-knowledge-driven diagnosis (DKD) method is proposed to identify the occurrence and cause variable in this paper. This proposed DKD method contains the following advantages. First, a data-driven detection model, using a recursive kernel principal component analysis (RKPCA) algorithm, is designed to capture the intrinsic nonlinear and time-varying characteristic of sludge bulking. Then, the occurrence of sludge bulking can be detected with high accuracy. Second, a DKD model, based on the Bayesian network (BN), is developed to extract the causality among process variables to identify the root cause variables of sludge bulking. Then, the root cause variables of sludge bulking can be diagnosed to improve the operation performance of WWTP. Finally, the proposed DKD method was tested on the measured data from a real WWTP. Experimental results confirmed the effectiveness of the proposed DKD method. Highlights: Detect the occurrence of sludge bulking from the water qualities by using RKPCA detection model. Diagnose the root cause variable of sludge bulking via the BN. This DKD method has been successfully used in a real wastewater treatment plant.